Technology Neutrality: Interaction between International Mobile Telecommunication and National Spectrum Management Policies - Mohamed El-Moghazi; Jason Whalley; James Irvine (International Telecommunications Society (ITS), 2015)
The Radio Sector of the ITU (ITU-R) has been involved in two aspects of personal mobile communication systems, namely defining the standards and identifying frequency bands related to these systems under the label of the International Mobile Telecommunication (IMT). This paper has investigated the influence of IMT standardisation activities in the ITU-R on national spectrum management policies with regard to decisions related to technology neutrality and technology selection. This paper has shown the different views on the importance of being one of the IMT technologies on regulator decision on technology selection, and has also revealed the elements in the IMT process that encourage and discourage more neutrality approach in technology selection. Moreover, different views on the mutual influence between the IMT definitions and 3G and 4G market definitions are highlighted. Furthermore, this paper has demonstrated how that the IMT spectrum identification has different positive influences on selecting technologies from the IMT family, which is mostly dependent on the country, and has also different positive and negative elements of influence on the tendency towards technology neutrality. In general, the paper shows that the international spectrum management regime does not prevent adopting technology neutrality, while having different elements of support and opposing regarding regulators' tendency towards technology neutrality.
Keywords: 330